2006
DOI: 10.1002/ajmg.b.30461
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence for linkage to chromosome 1q31‐32, 10q23.3, and 16p13.3 in a South African cohort with bipolar disorder

Abstract: Although the genetic variants predisposing to the development of bipolar disorder (BPD) have yet to be conclusively identified, replicated reports of linkage to particular chromosomal regions have been encouraging. Here we carried out a non-parametric linkage analysis of nine of these candidate loci in a unique South African sample of 47 BPD pedigrees (N = 350). Three polymorphic markers per region of interest (3 x 9) were typed in a Caucasian cohort of Afrikaner and British origin. Statistically significant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The loci on 1p13–31 and 1q25–31 implicated here have also both been reported to be involved in BP susceptibility [23,45,46,47,48,49,50]. The chromosome 1p13–31 region had been highlighted by our initial genome scan [10], and the present study has further strengthened this signal.…”
Section: Discussionsupporting
confidence: 79%
“…The loci on 1p13–31 and 1q25–31 implicated here have also both been reported to be involved in BP susceptibility [23,45,46,47,48,49,50]. The chromosome 1p13–31 region had been highlighted by our initial genome scan [10], and the present study has further strengthened this signal.…”
Section: Discussionsupporting
confidence: 79%
“…The search was performed in pub med for every chromosome separately with the key words: “Bipolar disorder, genetics, linkage, chromosome 1…X” and “Migraine, genetics, linkage, chromosome 1…X”, Table 3 displays all linkage loci that have been significantly or suggestively found in migraine linkage studies (Gardner et al, 1997; Nyholt et al, 1998a,b, 2000; Jones et al, 2001; Carlsson et al, 2002; Wessman et al, 2002; Lea et al, 2002; Björnsson et al, 2003; Soragna et al, 2003; Cader et al, 2003; Nyholt et al, 2005; Russo et al, 2005; Lea et al, 2005; Anttila et al, 2006), and the bipolar linkage studies (Savitz et al, 2007; Jamra et al, 2007; Zandi et al, 2007; Goes et al, 2007; Cassidy et al, 2007; Kerner et al, 2007; Jones et al, 2007; Etain et al, 2006; Marcheco-Teruel et al, 2006; Tomàs et al, 2006; Mukherjee et al, 2006; Schumacher et al, 2005; Hamshere et al, 2005; Lambert et al, 2005; McQueen et al, 2005; Kealey et al, 2005; Lin et al, 2005; Macgregor et al, 2004; Middleton et al, 2004; Fallin et al, 2004; Curtis et al, 2003; McInnis et al, 2003; Willour et al, 2003; Ewald et al, 2003; Ekholm et al, 2003; Ewald et al, 2002; Ekholm et al, 2002; Bailer et al, 2002; Dick et al, 2002; Cichon et al, 2001; Kelsoe et al, 2001; Radhakrishna et al, 2001; Detera-Wadleigh et al, 1999; Morissette et al, 1999; Ginns et al, 1998; Ewald et al, 1998; Detera-Wadleigh et al, 1997; Edenberg et al, 1997; Blackwood et al, 1996; Turecki et al, 1995; Pekkarinen et al, 1995) that have demonstrated overlapping or closely related linkage to these migraine loci. In addition we compared linkage studies in BPAD to the identified genes in FHM, and the BPAD (Jamra et al, 2007; Zandi et al, 2007; Hamshere et al, 2005; Middleton et al, 2004; Fallin et al, 2004; …”
Section: Discussionmentioning
confidence: 99%
“…The maximum occurred at marker D16S410 located at $19 megabasepairs (Mb) on chromosome 16. Within only 2 Mb of D16S410, five other studies also found linkage signals with BP [Foroud et al, 2000;Dick et al, 2002;Middleton et al, 2004;Cheng et al, 2006;Service et al, 2006], and a few other studies reported evidence for linkage nearby in the 16p11, 16p12, and 16p13 regions [McInnes et al, 1996;Edenberg et al, 1997;Cichon et al, 2001;Ewald et al, 2002;Ekholm et al, 2003;McQueen et al, 2005;Savitz et al, 2007] (see Fig. 1).…”
mentioning
confidence: 85%